The first study on clinicopathological changes in cats with feline infectious peritonitis with and without retrovirus coinfection - Wassamon Moyadee; Natdaroon Chiteafea; Supansa Tuanthap; Kiattawee Choowongkomon; Sittiruk Roytrakul; Oumaporn Rungsuriyawiboon; Chaiwat Boonkaewwan; Natthasit Tansakul; Amonpun Rattanasrisomporn; Jatuporn Rattanasrisomporn (Veterinary World, 2023)
Background and Aim: Feline infectious peritonitis (FIP) is an infectious, immune-mediated, and fatal disease in cats caused by a mutant feline coronavirus (FCoV) infection. Feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV) are two common retroviruses that play a role in reducing feline immune function with opportunistic retrovirus infection being a predisposing factor for the development of FIP. This study aimed to evaluate the clinicopathological parameters of FIP in cats with and without retrovirus coinfection.